2000
DOI: 10.1038/74865
|View full text |Cite
|
Sign up to set email alerts
|

Changing objects lead briefly flashed ones

Abstract: Continuous, predictable events and spontaneous events may coincide in the visual environment. For a continuously moving object, the brain compensates for delays in transmission between a retinal event and neural responses in higher visual areas. Here we show that it similarly compensated for other smoothly changing features. A disk was flashed briefly during the presentation of another disk of continuously changing color, and observers compared the colors of the disks at the moment of flash. We also tested lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 34 publications
4
109
0
3
Order By: Relevance
“…The motion aftereffect, an illusory motion percept seen on a static test pattern after prolonged motion adaptation, can displace the apparent position of static targets as well (Snowden, 1998;Nishida & Johnston, 1999). That spatial position is just as abstract a concept in neural terms as any other feature is also brought home by the findings of Sheth, Nijhawan, and Shimojo (2000), who reported the following. Suppose the color of one disk cycles continuously from, say, red to green and back.…”
Section: The Flash-lag Effectmentioning
confidence: 49%
“…The motion aftereffect, an illusory motion percept seen on a static test pattern after prolonged motion adaptation, can displace the apparent position of static targets as well (Snowden, 1998;Nishida & Johnston, 1999). That spatial position is just as abstract a concept in neural terms as any other feature is also brought home by the findings of Sheth, Nijhawan, and Shimojo (2000), who reported the following. Suppose the color of one disk cycles continuously from, say, red to green and back.…”
Section: The Flash-lag Effectmentioning
confidence: 49%
“…Motionlead terminology is inappropriate for yet another reason. It was recently shown that the phenomenon under discussion here also occurs for non-motion features such as luminance, color, and spatial frequency (Sheth et al 2000). The term flash-lag effect may be used without alteration to describe these non-motion-based effects.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, is movement itself even necessary? It can be replaced by the repetitive presentation of an invariant object 90 , and a phenomenon very similar to the flash-lag occurs in an experiment in which the colours of two spots are compared 91 . One spot gradually changes colour (say, from green to red), and the other spot is flashed in an intermediate colour (for example, orange) that exactly matches the colour of the changing spot at the instant of the flash.…”
Section: Discussionmentioning
confidence: 99%